Flexible bronchoscopy‐induced massive bleeding: A 12‐year multicentre retrospective cohort study. Issue 5 (8th April 2016) - Zhou, Guo‐Wu; Zhang, Wei; Dong, Yu‐Chao; Huang, Hai‐Dong; Hu, Chengping; Sun, Jiayuan; Jin, Faguang; Gu, Ye; Li, Qiang; Li, Shiyue
Abstract: Background and objective: Although massive bleeding is the most life‐threatening complication caused by flexible bronchoscopy, data on flexible bronchoscopy‐induced massive bleeding are scarce, and the associated clinical characteristics and prognostic factors are unknown. Methods: This was a multicentre retrospective cohort study of all patients who underwent flexible bronchoscopy in 33 tertiary hospitals from January 2001 to June 2013. The clinical characteristics and outcomes were collected and analysed. Results: A total of 194 patients with massive bleeding were identified among 520 343 patients who underwent flexible bronchoscopy. The average blood loss reached up to 378 mL. The overall incidence and mortality were 0.037% and 0.004%, respectively, and the overall fatality was 10.8%. The risk of massive bleeding induced by therapeutic bronchoscopies was significantly higher than that induced by diagnostic bronchoscopies (incidence: 0.059% vs 0.031%, P  < 0.001; mortality: 0.012% vs 0.003%, P  < 0.001; fatality: 20% vs 8.4%, P  = 0.068). Multivariate analysis showed that age ≥65 years, tracheal bleeding, blood loss ≥500 mL and occurrence of shock were independent factors predicting poor outcome, while emergency surgery was an independent protective factor. Re‐bleeding occurred in six patients, resulting in three deaths within a month. Conclusion: Flexible bronchoscopy‐induced massive bleeding is rare but life‐threatening. Age, bleeding location, bleeding volume, circulation condition and emergency surgery were independent prognostic factors. Abstract : There is a scarcity of information on the incidence and outcome of flexible bronchoscopy‐induced massive bleeding. In this large cohort study, the results indicated a low prevalence but high fatality of such bleeding. Age, bleeding location, bleeding volume, circulation condition and emergency surgery were independent prognostic factors.